ANALISIS DATA MINING UNTUK PENGARUH KUALITAS PELAYANAN, PENGIKLANAN, DAN HARGA TERHADAP KEPUTUSAN KONSUMEN DALAM MEMILIH PENJUAL ONLINE - Elfrin Hulu; Yonata Laia; Naomita Sihombing; Wandry Sitorus; Yuliani C. Simanjorang (Politeknik Bisnis Indonesia, 2023)
Almost everyone uses this buying option when selling online, for example, home appliances, fabrics, and many other products sold online. Some consumers complain that the service is still ineffective, and scams pretending to sell products sold through the site are common. As this study shows, many of the jobs humans do today can be done by computer systems. This study explores how to identify optimal online sales sites using the K-NN method. The aim is to prevent consumers from making mistakes when shopping online. It is hoped that this system will help visitors find simple and useful websites. All human activity must be innovative. This research has solved this problem and enabled the construction of an easy-to-use system. Based on calculations of load speed 2, page structure 3, interesting titles and content 4, short and recognizable links 5, and the results are useful.